Control and integration of sensory data - ODDSSON LARS I. E; WALL, III CONRAD; MEYER PETER FRANCIS (2012)
A sensory data integration system for integrating sensory data generated by a first sensory substitution device and sensory data generated by a second sensory substitution device. The system includes a processor configured to generate an orientation signal indicative of a difference between a subject's orientation and an acceptable orientation. The orientation signal is based on the sensory data generated by the first sensory substitution device and the sensory data generated by the second sensory substitution device.